2022
DOI: 10.3389/fpubh.2022.1019553
|View full text |Cite
|
Sign up to set email alerts
|

PrEP stigma among current and non-current PrEP users in Thailand: A comparison between hospital and key population-led health service settings

Abstract: BackgroundPre-exposure prophylaxis (PrEP) has demonstrated effectiveness in high-risk populations. PrEP service in Thailand became free of charge under the Universal Health Coverage (UHC) in 2021. The National Health Security Office launched a pilot project in 2020 to ensure sustainable service delivery, and the national monitoring and evaluation (M&E) framework was adopted to evaluate early phase implementation. We carried out a cross-sectional survey as part of the M&E process to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our findings indicated that some characteristics of PrEP pills may act as barriers to uptake. The effectiveness of PrEP in preventing HIV infection has been well documented, but it has also been used for HIV treatment, causing confusion between HIV prevention and treatment, which may lead clients to refuse to take it for fear of the HIV-related social stigma ( 47 ). Therefore, a different packaging or container for PrEP could be considered, and with a label indicating that is used for HIV prevention, to address the potential stigma ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that some characteristics of PrEP pills may act as barriers to uptake. The effectiveness of PrEP in preventing HIV infection has been well documented, but it has also been used for HIV treatment, causing confusion between HIV prevention and treatment, which may lead clients to refuse to take it for fear of the HIV-related social stigma ( 47 ). Therefore, a different packaging or container for PrEP could be considered, and with a label indicating that is used for HIV prevention, to address the potential stigma ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, key population led health services (KPLHS) provided PrEP for approximately two-thirds of the 13,769 PrEP clients in Thailand, 12 and PrEP use stigma appears lower among KPLHS PrEP clients than hospital PrEP clients. 34 Expanding combination HIV prevention interventions with PrEP through these organizations will require increasing the program space in which these providers operate and sustainability will require additional domestic funding. In addition to demonstrating the effectiveness and feasibility of this approach, building coalitions with multiple domestic and international stakeholders may support successful integration of key population based PrEP interventions into the national healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that stigma and discrimination directed against key populations most affected by HIV, including men who have sex with men, transgender individuals, people who use drugs and sex workers, also have been implicated in poorer HIV-related outcomes. In settings where they are discriminated against, members of key populations are less likely to test regularly for HIV, access preventative care such as pre-exposure prophylaxis, and are less likely to have access to risk reduction interventions such as substance recovery programmes and safer sex education [36][37][38][39]. Discriminatory treatment and marginalisation by policy makers and healthcare providers further deters individuals from accessing early screening and treatment [40].…”
Section: Reasons For Late Presentation To Carementioning
confidence: 99%